Multilingual Research Writing beyond English: The Case of Norwegian Academic Discourse in an Era of Multilingual Publication Practices - Kristin Solli; Ingjerd Legreid Ødemark (Publications, 2019)
Although English is the dominant language of scholarly publication, many multilingual scholars continue to publish in other languages while they also publish in English. A large body of research documents how these multilingual scholars negotiate writing in English for publication. We know less, however, about the implications of such negotiations for other languages that scholars work in. We wanted to investigate trends in writing conventions in language other than English during a period when multilingual publication patterns have been common. Specifically, we examined changes in rhetorical patterns in the introduction sections of the 1994 and the 2014 volumes of three Norwegian-language journals in three different disciplines in the humanities and social sciences. Our findings show that while certain features of our material might be interpreted as the result of a non-English discourse community adopting dominant Anglo-American models, the overall picture is more complex. Our study indicates that we need more research that examines cross-linguistic textual practices that focus on English and any other languages that scholars may work in. We also consider the possible pedagogical implications of such a focus.